Histone H3K4 methylation regulates hyphal growth, secondary metabolism and multiple stress responses in Fusarium graminearum - Liu, Ye; Liu, Na; Yin, Yanni; Chen, Yun; Jiang, Jinhua; Ma, Zhonghua (Environmental microbiology, 2015)
Histone H3 lysine 4 methylation (H3K4me) is generally associated with actively transcribed genes in a variety of eukaryotes. The function of H3K4me in phytopathogenic fungi remains unclear. Here, we report that FgSet1 is predominantly responsible for mono‐, di‐ and trimethylation of H3K4 in Fusarium graminearum. The FgSET1 deletion mutant (ΔFgSet1) was crippled in hyphal growth and virulence. H3K4me is required for the active transcription of genes involved in deoxynivalenol and aurofusarin biosyntheses. Unexpectedly, FgSet1 plays an important role in the response of F. graminearum to cell wall‐damaging agents via negatively regulating phosphorylation of FgMgv1, a core kinase in the cell wall integrity pathway. In addition, ΔFgSet1 exhibited increased resistance to the transcription elongation inhibitor mycophenolic acid. Yeast two‐hybrid assays showed that FgSet1 physically interacts with multiple proteins including FgBre2, FgSpp1 and FgSwd2. FgBre2 further interacts with FgSdc1. Western blotting analyses showed that FgBre2 and FgSdc1 are associated with H3K4me. Both proteins are also involved in regulating deoxynivalenol biosynthesis and in responses to mycophenolic acid and cell wall‐damaging agents. Taken together, these data indicate that H3K4me plays critical roles not only in regulation of fungal growth and secondary metabolism but also in multiple stress responses in F. graminearum.